Hexacyanoferrate(II) as an Oxidant for the Titrimetric Determination of Benzoyl Hydrazine - Rambabu, C.; Bhaskara Rao, K.; Somasekhara Rao, K. (Asian Journal of Chemistry, 2010)
In the present note, the authors report the results of titrimetric determination of benzoyl hydrazine with hexacyanoferrate(III) in alkaline medium.